Farming Learning Berbasis Pembelajaran Terpadu: Solusi Pembelajaran Pandemi di SD NU Master Sokaraja Banyumas - Munasiroh, Munasiroh (J-PGMI: Jurnal Pendidikan Guru MI, 2023)
Pandemic learning has become scary homework for teachers, students and parents who are not ready. Therefore, schools need to facilitate integrated project-based learning that can be translated by parents into a flexible learning model so that it can synergize distance learning at home. One of them is farming learning carried out by SD NU Master Sokaraja. This research uses a descriptive qualitative method based on field research. Data collection techniques use observation, interviews and documentation. The research subjects are students, teachers and parents of class I C. The research object is farming learning based on integrated learning: pandemic learning solutions at SD NU Master Sokaraja Banyumas. The results of the research show that the implementation of farming learning takes the first form, planning, namely the teacher compiling literacy in the form of a booklet with information on plants and how to plant them, providing farming materials, and mapping indicators which are outlined in student observation sheets. Second, implementation, namely teachers are interactive and continuous in monitoring and providing assistance via Zoom and WhatsApp. Third, the teacher carries out an evaluation in the form of assessment and follow-up on the results of student observation sheets. Through this farming learning activity, students can equip students with life skills in processing literacy information from guide booklets, how to care for plants and process the harvest.